Struggling to stay and struggling to leave: The experiences of elite para-athletes at the end of their sport careers - Bundon, A.; Ashfield, A.; Smith, B.; Goosey-Tolfrey, V. (Psychology of Sport and Exercise, 2018)
To explore the retirement experiences of elite para-athletes. Athletic retirement has long been of interest to sport psychologists. With a few exceptions, little attention has been paid to the retirements of elite athletes with disabilities. The research that has been done on para-sport was conducted in the late 1990s and the context of Paralympic sport has changed in the interim. DESIGN: An online survey was distributed to retired para-athletes (n=60) and qualitative interviews were conducted with a purposive sub-sample (n=13). SAMPLE: The sample included 48 Paralympians (21 had medalled at the Paralympic Games) and 12 internationally competitive para-athletes. The group included 39 males and 21 females and was diverse in age (22 to 77 years of age), impairment history and impairment type (35 acquired impairments and 25 congenital impairments), and sport (24 different para-sports). METHODS: Guided by a subjective and transactional epistemological framework, data was thematically analyzed. RESULTS: Although most para-athletes leave sport for the same reasons as their able-bodied peers, certain reasons for retirement, such as declassification, are unique to para-sport. Para-athletes facing these types of retirements had particularly difficult transition experiences and could benefit from additional support. Para-athletes also reported that the increasing professionalization of para-sport, combined with uncertainty about post-sport employment opportunites for people with disabilities, made it more difficult to retire. CONCLUSIONS: Understanding the experiences of retirement that are unique to para-sport will permit sport psychologists and other practitioners to provide better and more targeted support to para-athletes.